2013
DOI: 10.3389/fpsyg.2013.00616
|View full text |Cite
|
Sign up to set email alerts
|

The IAT shows no evidence for Kandinsky's color-shape associations

Abstract: In the early twentieth century, the Bauhaus revolutionized art and design by using simple colors and forms. Wassily Kandinsky was especially interested in the relationship of these two visual attributes and postulated a fundamental correspondence between color and form: yellow triangle, red square and blue circle. Subsequent empirical studies used preference judgments to test Kandinsky's original color-form combinations, usually yielding inconsistent results. We have set out to test the validity of these postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 26 publications
5
57
0
Order By: Relevance
“…Thus, Kandinsky's nonfigurative paintings and theory of synesthesia [ 53 ], prompted by his experience of extraordinary visions of lines and colors elicited by the sound of musical instruments, paved the way to abstract art and thus marked a turning point in history of art [ 47 ]. A recent analysis of Kandinsky's works using the Implicit Association Test found no implicit association between the original color–form combinations, and authors concluded that these are probably not a universal property of the visual system [ 44 ].…”
Section: Painters’ Comprehension Of Synesthesiamentioning
confidence: 99%
“…Thus, Kandinsky's nonfigurative paintings and theory of synesthesia [ 53 ], prompted by his experience of extraordinary visions of lines and colors elicited by the sound of musical instruments, paved the way to abstract art and thus marked a turning point in history of art [ 47 ]. A recent analysis of Kandinsky's works using the Implicit Association Test found no implicit association between the original color–form combinations, and authors concluded that these are probably not a universal property of the visual system [ 44 ].…”
Section: Painters’ Comprehension Of Synesthesiamentioning
confidence: 99%
“…In addition to the direct matching tasks in the aforementioned studies, some studies have adopted indirect behavioral measures to investigate color-shape associations. Moreover, studies using indirect behavioral methods have also failed to find clear evidence for Kandinsky’s color-shape associations [ 9 11 ]. Kharkhurin revisited Kandinsky’s color-shape associations in two experiments: one used with a priming technique and the other used a recognition test.…”
Section: Introductionmentioning
confidence: 99%
“…Kandinsky maintained that the triangle/tetrahedron is yellow, the square/cube is red, and the circle/sphere is blue. In our courses we play with Kandinsky's questionnaire and discuss the results but are quick to explain that there is absolutely no scientific proof for this theory …”
Section: Colour Science For the Nonscientists—what To Teach And What mentioning
confidence: 99%
“…In our courses we play with Kandinsky's questionnaire and discuss the results but are quick to explain that there is absolutely no scientific proof for this theory. [54][55][56]…”
Section: Colour and Formmentioning
confidence: 99%